INNOVATIONS OF INDONESIAN LANGUAGE AND LITERATURE LEARNING IN THE ERA OF SOCIETY 5.0. - Emawati, Emawati (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2020)
The purpose of this article was to describe in depth some of the innovations Indonesian language and literature learning in the era of society 5.0. Innovation of Indonesian language and literature learning is important to do because it is relevant to the vision of society 5.0, namely, to create learning transformation. In this era of society 5.0, people become controllers of technology and society is required to think critically, constructively and innovatively. Language as a medium for expressing thoughts, ideas, and feelings can form people's behavior. The behavior is expected to contribute to the learning of Indonesian language and literature and is relevant to the needs of society 5.0. To achieve this goal there are several innovations that can be performed, namely the implementation of HOTS (High Order Thinking Skills), renewal of futuristic learning orientation, determination of appropriate learning models, development of teacher and lecturer competencies, provision of infrastructure and futuristic learning resources.Keywords: society 5.0., learning innovation, futuristic